Cardioprotective Effects of SIRT6 in a Mouse Model of Transverse Aortic Constriction-Induced Heart Failure - Li, Yongming; Meng, Xianda; Wang, Wenguang; Liu, Fu; Hao, Zhiru; Yang, Yang; Zhao, Jinbo; Yin, Wensi; Xu, Lijuan; Zhao, Ruiping; Hu, Jiang (Frontiers in Physiology, 2017)
SIRT6, a member of the NAD (+)-dependent class III deacetylase sirtuin family, plays important roles in the maintenance of cardiovascular homeostasis. Telomere shortening is a risk factor for age-associated diseases, including heart disease. In the present study, we investigated the role of SIRT6 and telomerase in a mouse model of transverse aortic constriction (TAC)-induced heart failure. SIRT6, telomerase reverse transcriptase (TERT), and telomere repeat binding factor (TRF)-1were significantly downregulated in TAC mice compared with their expression in sham-operated mice. Lentiviral vector-mediated overexpression of SIRT6 upregulated TERT and TRF1 and increased the survival of mice after TAC. Echocardiography and hemodynamic measurements as well as histological analyses indicated that SIRT6 overexpression attenuated TAC-induced heart dysfunction and decreased TAC-induced cardiac inflammatory responses, reducing cardiac fibrosis and decreasing infarct size. Taken together, our findings indicate that SIRT6 protects the myocardium against damage and this effect may be mediated by the modulation of telomeres. Our findings linking SIRT6 and telomere integrity in the heart warrant further investigation into the underlying mechanisms and support SIRT6 as a promising therapeutic target for the treatment of cardiovascular diseases.